The Influence Of Intrinsic And Extrinsic Motivation On Employee Engagement And Job Satisfaction In The Snack Food Industry - Novianti, Intan Erlita; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to prove that there is a relationship between all the variables assumed to occur in the snack food industry employees in West Jakarta and Central Jakarta which consist of the variables intrinsic motivation, extrinsic motivation, employee involvement and job satisfaction. The research approach used in this research is quantitative research. The population in this study are employees who work in the snack industry in West Jakarta and Central Jakarta. Data was collected using a survey method by distributing questionnaires to respondents, namely snack food industry employees with a working period of more than 1 year at the age of 21 years to 55 years. Questionnaires were collected as many as 209 respondents, the data was then processed using Smart PLS. Based on the results of the analysis it is known that the variable. Partially, the Intrinsic Motivation and Extrinsic Motivation variables are proven to have a positive effect on Employee Engagement and Job Satisfaction. Most of the respondents feel that the motivation provided by the Company can increase morale which strengthens employee engagement and job satisfaction. Keywords: Intrinsic Motivation, Extrinsic Motivation, Employee Involvement, Job Satisfaction